The Effect of Training, Career Development, Empowerment and Work Discipline on Job Satisfaction at Class I Airport Operator Unit of Mopah Merauke - Blasius Basa; Anita Erari; Made Yudhi Setiani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of training, career development, empowerment, and work discipline on employee job satisfaction at the Class I Airport Operator unit of Mopah Merauke. The research involved 102 employees at the Class I Airport Operator unit of Mopah Merauke as the research sample. Data were collected using a questionnaire and then tabulated and analyzed using multiple linear regressions with the aid of SPSS 21. The analysis proves that training, career development, and empowerment have a significant effect on job satisfaction, while work discipline has no significant effect on job satisfaction.